The Ability of Different Grass Root’s Soil at the Entrance of Pagoh Hub - KAMAL, EZANI FIZAFARISHA; JAMIAN, MUHAMMAD AIMAN; MOHD ZAHIR, MUHAMMAD MIFDHAL AKIF; SUWANDI, AMIR KHAN (Multidisciplinary Applied Research and Innovation, 2022)
This case studied the performance of grass roots in stability of slope at Pagoh Hub entrance between 3 main soil conditions at Pagoh Hub. Namely; Vertiver grass’ soil, Cow grass’ soil with 3 samples each and 1 unrooted soil taken as samples to check the soil performance. The objective of the project is to analyse the effect of different types of grass roots on the stability of soil slope. Profiles of slopes were obtained from previous study. Basic measurements and calculation have been made on the samples to obtain basic geotechnical parameters such as atterberg limits, specific gravity and natural moisture content. In addition, cohesion, internal friction angle, and unit weight of the soil are calculated in order to run GeoSlope software in obtaining slope safety factor. From all 7 sites; 3 sites from Vertiver grass, 3 sites from Cow grass and 1 site of unrooted soil, we can conclude that Vertiver grass has the best performance as it reaches the highest value in every measurement, followed by Cow grass and unrooted soil. Vertiver grass is the most suitable grass to maintain the slopes stability.